De la vulnérabilité à la résilience : mutation ou bouleversement ? - Bruno Barroca; Maryline DiNardo; Irène Mboumoua (EchoGéo)
Vulnerability and resilience are two concepts which have emerged successively to analyze and characterize risks. The concept of vulnerability was the dominant paradigm in risk assessment. Since the 2000s, resilience is appearing in geography and urban planning especially since the concept of vulnerability is showing some limits in understanding risks. To exist, the concept of resilience has evolved to become a more operational concept in urban risk analysis. This paper emphasizes the semantic shift that has occurred between vulnerability and resilience. Its purpose is to analyze why the concept of resilience is imposing itself. Through database analysis, we highlight that the use of this concept is limited till the mid 2000s and then is diffused rapidly. Then, we will try to formulate hypotheses to explain the semantic shift from vulnerability to resilience. Finally, we will emphasize the risk of instrumentalisation of the concept of resilience by urban planning actors.